2003
DOI: 10.1590/s0100-41582003000300009
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic diversity among brazilian isolates of Macrophomina phaseolina revealed by RAPD

Abstract: Macrophomina phaseolina has been considered one of the most prevalent soybean (Glycine max) pathogens in Brazil. No genetic resistance has been determined in soybean and very little is known about the genetic diversity of this pathogen in tropical and sub-tropical regions. Fifty-five isolates from soybean roots were collected in different regions and analyzed through RAPD for genetic diversity. The UPGMA cluster analysis for 74 loci scored permitted identification of three divergent groups with an average simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 9 publications
4
50
2
1
Order By: Relevance
“…The results of the present study clearly demonstrated that M. phaseolina from different parts of the country were highly variable and ISSR markers are suitable to reflect the genetic diversity among the populations. A number of molecular studies elsewhere have shown a high level of polymorphism in this fungus when isolates from different host or geographical origins were compared using different molecular tools (Almeida et al, 2003;Jones et al, 1998;Mayek-Perez et al, 2001;Su et al, 2001;Vandemark et al, 2000). Other recent studies have demonstrated the genetic diversity among M. phaseolina isolates (Aboshosha et al, 2007;Aghakhani and Dubey, 2009;Babu et al, 2010;Baird et al, 2010;Beas-Fernandez et al, 2006;Das et al, 2006;Jana et al, 2005a;Jana et al, 2005b;Omar et al, 2007;Purkayastha et al, 2008;Rajkumar and Kuruvinashetti, 2007;Reyes-Franco et al, 2006;Saleh et al, 2010).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of the present study clearly demonstrated that M. phaseolina from different parts of the country were highly variable and ISSR markers are suitable to reflect the genetic diversity among the populations. A number of molecular studies elsewhere have shown a high level of polymorphism in this fungus when isolates from different host or geographical origins were compared using different molecular tools (Almeida et al, 2003;Jones et al, 1998;Mayek-Perez et al, 2001;Su et al, 2001;Vandemark et al, 2000). Other recent studies have demonstrated the genetic diversity among M. phaseolina isolates (Aboshosha et al, 2007;Aghakhani and Dubey, 2009;Babu et al, 2010;Baird et al, 2010;Beas-Fernandez et al, 2006;Das et al, 2006;Jana et al, 2005a;Jana et al, 2005b;Omar et al, 2007;Purkayastha et al, 2008;Rajkumar and Kuruvinashetti, 2007;Reyes-Franco et al, 2006;Saleh et al, 2010).…”
Section: Resultsmentioning
confidence: 98%
“…Different molecular methods have been used for differentiating M. phaseolina populations including Restriction Fragment Length Polymorphism (RFLP) of rDNA-ITS regions (Aghakhani and Dubey, 2009;Almeida et al, 2003;Purkayastha et al, 2006;Su et al, 2001), Random Amplified Polymorphic DNA (RAPD) (Aboshosha et al, 2007;Aghakhani and Dubey, 2009;Almeida et al, 2003;Almeida et al, 2008;Babu et al, 2010;Das et al, 2006;Jana et al, 2003;Omar et al, 2007;Purkayastha et al, Rajkumar and Kuruvinashetti, 2007;Su et al, 2001;Zade et al, 2009), Amplified Fragment Length Polymorphism (AFLP) (Brooker et al, 2008;Mayek-Perez et al, 2001;Reyes-Franco et al, 2006;Saleh et al, 2010;Vandemark et al, 2000), Universal Rice Primer PCR (URP-PCR) (Jana et al, 2005b), Inter simple sequence repeats (ISSR) (Jana et al, 2005a;Purkayastha et al, 2008), Repetitive SequenceBased Polymerase Chain Reaction (Rep-PCR) (Purkayastha et al, 2008) and SSR (Baird et al, 2010). Inter simple sequence repeat (ISSR) markers are powerful tools which can be utilized to access the variation in the flanking regions of microsatellite loci that are dispersed throughout all genomes (Zietkiewicz et al, 1994).…”
mentioning
confidence: 99%
“…It has been frequently employed to perform an easy assessment of isolate aggressiveness (Shekhar et al 2006). Phenotypic as well as genetic variation in the pathogen population, even from the same geographical region, has been documented, adding difficulties to the implementation of successful management strategies (Almeida et al 2003;Purkayastha et al 2006;Kaur et al 2012;Mahmoudi and Ghashghaie 2013;Almeida et al 2014). The use of highly aggressive isolates is recommended to optimize the results of screening assays (Mahmoudi and Ghashghaie 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Isolates having morphological similarity are not necessarily identical genetically, they might have some differences. The variable genetic pattern contributes to variation in morphology and pathogenesis, which has been confirmed by using different molecular tools (Mayek-P´erez et al, 2001;ReyesFranco et al, 2006;Almeida et al, 2003 andJana et al, 2003).As the pathogen has no sexual phase, genetic diversity is produced either by fusion of vegetative cells or by parasexual recombination between nuclear genes (Carlile, 1986). In nature genetic variability improves survival of a fungus (Bashasab, and Kuruvinashetti, 2007).…”
Section: Genotypementioning
confidence: 96%